Kerajinan Anyaman Purun sebagai Warisan Turun Temurun Masyarakat Tanjung Atap, Ogan Ilir - Syarifuddin Syarifuddin; Supriyanto Supriyanto; Chindi Ayu Shonia; Mailiza Hidayati (LP4MK STKIP PGRI Lubuklinggau, 2022)
The purpose of this research is to discuss about purun woven from Tanjung Atap village which is a hereditary heritage in the Tanjung Atap village community. The method used in this research is qualitative research. The result of this research is that purun weaving has existed since ancient times and continues to be preserved by being taught from generation to generation. This purun weaving activity has been attached to the daily activities of the residents of Tanjung Atap village. This is evidenced by the existence of purun woven in the village of Tanjung Atap. Once during the monetary crisis and the sale of webbing was difficult, the craftsmen switched to other jobs. However, purun weaving is still done on the sidelines of free time. Along with the times, purun woven products were originally only in the form of mats, now purun woven products have varied from bags, wallets, laptop bags, trash cans, slippers, and many more. This happened because of the guidance given to 20 residents of Tanjung purun village to be creative with purun woven, this coaching was led by Mrs. Karyani in collaboration with Sriwijaya University. The purpose of this research is to discuss about purun woven from Tanjung Atap village which is a hereditary heritage in the Tanjung Atap village community. The method used in this research is qualitative research. The result of this research is that purun weaving has existed since ancient times and continues to be preserved by being taught from generation to generation. This purun weaving activity has been attached to the daily activities of the residents of Tanjung Atap village. This is evidenced by the existence of purun woven in the village of Tanjung Atap. Once during the monetary crisis and the sale of webbing was difficult, the craftsmen switched to other jobs. However, purun weaving is still done on the sidelines of free time. Along with the times, purun woven products were originally only in the form of mats, now purun woven products have varied from bags, wallets, laptop bags, trash cans, slippers, and many more. This happened because of the guidance given to 20 residents of Tanjung purun village to be creative with purun woven, this coaching was led by Mrs. Karyani in collaboration with Sriwijaya University.